STRATEGIES FOR TEACHING ENGLISH IN INCLUSIVE CLASSROOMS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article explores effective strategies for teaching English in inclusive classrooms where learners demonstrate diverse cognitive, linguistic, and physical characteristics. It focuses on differentiated instruction, assistive technology, collaborative learning, and adaptive assessment. The study highlights the importance of flexibility, accessibility, and learner-centered pedagogy in ensuring equal participation and improving educational outcomes.